THE IMPLEMENTATION OF RITUAL COMMUNICATION IN THE PERSPECTIVE OF RELIGIOUS TOLERANCE AT THE SARASUTA HOLY PLACE - I Ketut Sumada; I Wayan Ardhi Wirawan (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
This article aims to explain the implementation of ritual communication carried out by the Balinese-Hindu and Sasak-Islamic people at the Sarasuta holy place, Lingsar Subsubdistrict, West Lombok Regency from the perspective of religious tolerance. The method used in producing this study is interpretive qualitative using a case study model. Based on the research results found three findings. First, ritual communication presented by followers of two different religions, namely Sasak-Islam and Balinese-Hindu as the implementation of a belief system to improve the quality of life. Second, the Muslim-Sasak community carries out ritual communication as the implementation of the customary traditions inherited by their predecessors, while the Balinese-Hindu community implements ritual communication as the continuation of Hindu religious culture. Third, the ritual communication of people of different religions in the Sarasuta holy place in the social dimension tends to strengthen religious tolerance.